The Combination Therapy of Dietary Galacto-Oligosaccharides With Budesonide Reduces Pulmonary Th2 Driving Mediators and Mast Cell Degranulation in a Murine Model of House Dust Mite Induced Asthma - Verheijden, Kim A. T.; Braber, Saskia; Leusink-Muis, Thea; Jeurink, Prescilla V.; Thijssen, Suzan; Kraneveld, Aletta D.; Garssen, Johan; Folkerts, Gert; Willemsen, Linette E. M. (Frontiers in Immunology, 2018)
Background: Dietary non-digestible galacto-oligosaccharides (GOS) suppress allergic responses in mice sensitized and challenged with house dust mite (HDM). Budesonide is the standard therapy for allergic asthma in humans but is not always completely effective. Aim: To compare the efficacy of budesonide or different doses of GOS alone or with a combination therapy of budesonide and GOS on HDM-allergic responses in mice. Methods: BALB/c mice were sensitized and challenged with HDM, while fed a control diet or a diet supplemented with 1 or 2.5 w/w% GOS, and either or not oropharyngeally instilled with budesonide. Systemic and local inflammatory markers, such as mucosal mast cell protease-1 (mMCP-1) in serum, pulmonary CCL17, CCL22 and IL-33 concentrations and inflammatory cell influx in the bronchoalveolar lavage fluid (BALF) were determined. Results: Budesonide or GOS alone suppressed the number of eosinophils in the BALF of HDM allergic mice whereas budesonide either or not combined with GOS lowered both eosinophil and lymphocyte numbers in the BALF of HDM-allergic mice. Both 1 w/w% and 2.5 w/w% GOS and/or budesonide suppressed serum mMCP-1 concentrations. However, budesonide nor GOS alone was capable of reducing Th2 driving chemokines CCL17, CCL22 and IL-33 protein levels in supernatants of lung homogenates of HDM allergic mice, whereas the combination therapy did. Moreover, IL-13 concentrations were only significantly suppressed in mice treated with budesonide while fed GOS. A similar tendency was observed for the frequency of GATA3+CD4+ Th2 and CD4+RORγt+ Th17 cells in the lungs of the allergic mice. Conclusion: Dietary intervention using GOS may be a novel way to further improve the efficacy of anti-inflammatory drug therapy in allergic asthma by lowering Th2 driving mediators and mast cell degranulation.